2020
DOI: 10.4314/ejhs.v30i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes of Placenta Associated with Maternal Anaemia in Northeast Ethiopia: A Comparative Study

Abstract: BACKGROUND: Anaemia during pregnancy affects about half of all pregnant mothers in developing countries; it is the major causes of indirect maternal mortality. Anaemia can directly cause poor growth of fetus in utero due to inadequate oxygen flow to the placental tissue or it is indirect indicator of maternal nutritional deficiency. Mal-development of placenta is the leading cause of maternal and perinatal mortality and an important factor of fetal growth retardation. The aim of this study was to compare histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Capillary dilatation was accompanied by villous hypervascularity (increased number of capillaries per villus), in proportion to vessel dilation. Pathological evidence of FVM was earlier shown in many different studies (12,25,27,44,(57)(58)(59)(60)(61)(62), however, the severity of changes observed in our study was not seen in other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Capillary dilatation was accompanied by villous hypervascularity (increased number of capillaries per villus), in proportion to vessel dilation. Pathological evidence of FVM was earlier shown in many different studies (12,25,27,44,(57)(58)(59)(60)(61)(62), however, the severity of changes observed in our study was not seen in other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…The placenta with inadequate vascularization expands to cover the entire birth canal (DS & Bird, 2017;Woods et al, 2018). In pregnant women, a deficiency of Hb levels can result in diminished placental vascularity (Gebremeskel et al, 2020;Rai & Cross, 2014). Observing the results of the initial survey and the data from the obstetrical medical record section at Sultan Agung Islamic Hospital, Semarang, the incidence of placenta previa has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, expectant gravida patients who have a chance of developing placenta previa will be closely watched and transferred to hospitals with more advanced equipment. Support pregnant women's health by reducing the risk of placenta previa, one of which is caused by reduced vascularity in the placenta (Delli Pizzi et al, 2019;Firmansyah, 2017) that can be caused by a lack of Hb levels in pregnant women (Gebremeskel et al, 2020;Rai & Cross, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The placenta with insufficient vascularization then expands to cover all parts of the birth canal (DS & Bird, 2017;Woods et al, 2018). Reduced vascularity in the placenta can be caused by a lack of Hb levels in pregnant women (Gebremeskel et al, 2020;Rai & Cross, 2014). Seeing from the results of the initial survey by observing the data from the obstetrical medical record section at RSI Sultan Agung Semarang, there was an increase in the incidence of placenta previa.…”
Section: Correlation Of Hb Levels and Incidence Of Placenta Previamentioning
confidence: 99%